2000
DOI: 10.1093/ajcn/71.6.1570
|View full text |Cite
|
Sign up to set email alerts
|

Maternal low-dose vitamin A or β-carotene supplementation has no effect on fetal loss and early infant mortality: a randomized cluster trial in Nepal

Abstract: Background:The effect of vitamin A supplementation on the survival of infants aged < 6 mo is unclear. Because most infant deaths occur in the first few month of life, maternal supplementation may improve infant survival. Objectives: The objective was to assess the effect of maternal vitamin A or ␤-carotene supplementation on fetal loss and survival of infants < 6 mo of age. Design: Married women of reproductive age in 270 wards of Sarlahi district, Nepal, were eligible to participate. Wards were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
7

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 36 publications
3
58
1
7
Order By: Relevance
“…This is in line with the findings of Katz et al, (2000), who found that foetal loss and early infant mortality were not reduced when Nepalese women were supplemented weekly with vitamin A during pregnancy. However vitamin A supplementation was beneficial in terms of reducing mortality in pregnant women (West et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with the findings of Katz et al, (2000), who found that foetal loss and early infant mortality were not reduced when Nepalese women were supplemented weekly with vitamin A during pregnancy. However vitamin A supplementation was beneficial in terms of reducing mortality in pregnant women (West et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Inadequate maternal nutrition during pregnancy is thought to be one of the contributors to this (Frongillo, 1999;Waterlow & Schürch, 1994;Kusin et al, 1992). Vitamin A supplementation of women before and during pregnancy has been shown to reduce maternal nightblindness and mortality (West et al, 1999;Christian et al, 1998) and improve serum retinol levels in infants (Katz et al, 2000;Schmidt et al, 2001). However it did not reduce foetal loss or early infant mortality (Katz et al, 2000) and other outcomes of infants have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In the low-lying plains of Nepal, called 'Terai,' mortality related to pregnancy was as high as 704 deaths per 100 000 live births (West et al, 1999), being 100 times higher than that of Japan, that is, 7.3 in 2002 (Health andWelfare Statistics Association, 2004). The 24-week infant mortality rate in this area was 70.8 per 1000 live births (Katz et al, 2000), more than 10 times higher than that in the developed world. Katz et al (2003) pointed out that maternal undernutrition during pregnancy was strongly associated with infant mortality and Christian et al (2004) revealed potential effects of intervention by means of supplementation of micronutrients on improvement of maternal and infant health and survival.…”
Section: Introductionmentioning
confidence: 63%
“…27 Maternal vitamin A supplementation significantly reduced maternal mortality in Nepal by 40%, 28 although there was no impact on infant mortality through age 6 months. 29 Vitamin A supplementation early in the newborn period, however, is under evaluation as a potentially promising approach. 30 Several trials suggest calcium supplementation can lower rates of preterm delivery and might be effective in preventing pre-eclampsia.…”
Section: Maternal Nutritionmentioning
confidence: 99%